Immunological changes associated with adenomyosis: a systematic review. (25th October 2020) - Bourdon, M; Santulli, P; Jeljeli, M; Vannuccini, S; Marcellin, L; Doridot, L; Petraglia, F; Batteux, F; Chapron, C
Abstract: BACKGROUND: Adenomyosis is a benign gynecological disorder associated with subfertility, pelvic pain and abnormal uterine bleeding that have significant consequences for the health and quality of life of women. Histologically, it is defined as the presence of ectopic endometrial islets within the myometrium. Its pathogenesis has not yet been elucidated and several pieces of the puzzle are still missing. One process involved in the development of adenomyosis is the increased capacity of some endometrial cells to infiltrate the myometrium. Moreover, the local and systemic immune systems are associated with the onset of the disease and with maintaining it. Numerous observations have highlighted the activation of immune cells and the release of immune soluble factors in adenomyosis. The contribution of immunity occurs in conjunction with hormonal aberrations and activation of the epithelial to mesenchymal transition (EMT) pathway, which promotes migration of endometrial cells. Here, we review current knowledge on the immunological changes in adenomyosis, with the aim of further elucidation of the pathogenesis of this disease. OBJECTIVE AND RATIONALE: The objective was to systematically review the literature regarding the role of the immune system in development of adenomyosis in the inner and the outer myometrium, in humans. SEARCH METHODS: A systematic review of published human studies was performed in MEDLINE, EMBASE and Cochrane Library databases from 1970 to February 2019 using the combination of Medical Subject Headings (MeSH): Adenomyosis AND ('Immune System' OR 'Gonadal Steroid Hormones'), and free-text terms for the following search terms (and their variants): Adenomyosis AND (immunity OR immune OR macrophage OR 'natural killer cell' OR lymphocyte* OR leucocyte* OR HLA OR inflammation OR 'sex steroid' OR 'epithelial to mesenchymal transition' OR 'EMT'). Studies in which no comparison was made with control patients, without adenomyosis (systemic sample and/or eutopic endometrium), were excluded. OUTCOMES: A total of 42 articles were included in our systematic review. Changes in innate and adaptive immune cell numbers were described in the eutopic and/or ectopic endometrium of women with adenomyosis compared to disease-free counterparts. They mostly described an increase in lymphocyte and macrophage cell populations in adenomyosis eutopic endometrium compared to controls. These observations underscore the immune contributions to the disease pathogenesis. Thirty-one cytokines and other markers involved in immune pathways were studied in the included articles. Pro-inflammatory cytokines (interleukin (IL) 6, IL1β, interferon (IFN) α, tumor necrosis factor α, IFNγ) as well as anti-inflammatory or regulatory mediators (IL10, transforming growth factor β…) were found to be elevated in the eutopic endometrium and/or in the ectopic endometrium of the myometrium in women with adenomyosis compared to controls. Moreover, in women affected by adenomyosis, immunity was reported to be directly or indirectly linked to sex steroid hormone aberrations (notably changes in progesterone receptor in eutopic and ectopic endometrium) in three studies and to EMT in four studies. WIDER IMPLICATIONS: The available literature clearly depicts immunological changes that are associated with adenomyosis. Both systemic and local immune changes have been described in women affected by adenomyosis, with the coexistence of changes in inflammatory as well as anti-inflammatory signals. It is likely that these immune changes, through an EMT mechanism, stimulate the migration of endometrial cells into the myometrium that, together with an endocrine imbalance, promote this inflammatory process. In light of the considerable impact of adenomyosis on women's health, a better understanding of the role played by the immune system in adenomyosis is likely to yield new research opportunities to better understand its pathogenesis.